Estimativas de uma função de exportações para o Estado do Ceará - Kloeckner, Rafael (2013)
The total value of annual exports of the Brazilian State of Ceará increased by an average 8.7% per year between 1990 and 2012. This study aims to estimate an export function for this state. The econometric methodology employed is based on the cointegration analysis proposed by Johansen (1988). Different conditioning factors of theoretical functions of supply and demand for exports were considered as explanatory variables. The results presented, in terms of signs and magnitudes of the estimated elasticities, are consistent both in terms of economic theory and empirical studies conducted in Brazil. The error correction model indicated that the exchange rate has little importance in explaining the growth rate of exports in the short term. In the best approximation to the long-term relationship, the estimated cointegration vector suggests that foreign income is more important than the exchange rate to explain the growth of exports. These results appear to indicate that public policies for the export sector could be more focused on improvements in meeting demand (investment in the port sector, for example) and less focused on short-term exchange rate policy.